Promoting the Performance of Li–CO2 Batteries via Constructing Three-Dimensional Interconnected K+ Doped MnO2 Nanowires Networks - Tang, Zhuolin; Yuan, Mengming; Zhu, Huali; Zeng, Guang; Liu, Jun; Duan, Junfei; Chen, Zhaoyong (Frontiers in Chemistry, 2021)
Nowadays, Li–CO2 batteries have attracted enormous interests due to their high energy density for integrated energy storage and conversion devices, superiorities of capturing and converting CO2. Nevertheless, the actual application of Li–CO2 batteries is hindered attributed to excessive overpotential and poor lifespan. In the past decades, catalysts have been employed in the Li–CO2 batteries and been demonstrated to reduce the decomposition potential of the as-formed Li2CO3 during charge process with high efficiency. However, as a representative of promising catalysts, the high costs of noble metals limit the further development, which gives rise to the exploration of catalysts with high efficiency and low cost. In this work, we prepared a K+ doped MnO2 nanowires networks with three-dimensional interconnections (3D KMO NWs) catalyst through a simple hydrothermal method. The interconnected 3D nanowires network catalysts could accelerate the Li ions diffusion, CO2 transfer and the decomposition of discharge products Li2CO3. It is found that high content of K+ doping can promote the diffusion of ions, electrons and CO2 in the MnO2 air cathode, and promote the octahedral effect of MnO6, stabilize the structure of MnO2 hosts, and improve the catalytic activity of CO2. Therefore, it shows a high total discharge capacity of 9043 mAh g-1, a low overpotential of 1.25 V, and a longer cycle performance.